2022
DOI: 10.1371/journal.pone.0262224
|View full text |Cite
|
Sign up to set email alerts
|

Selective neurodegeneration of the hippocampus caused by chronic cerebral hypoperfusion: F-18 FDG PET study in rats

Abstract: Background Chronic cerebral hypoperfusion (CCH) is known to induce Alzheimer’s disease (AD) pathology, but its mechanism remains unclear. The purpose of this study was to identify the cerebral regions that are affected by CCH, and to evaluate the development of AD pathology in a rat model of CCH. Methods A rat model of CCH was established by bilaterally ligating the common carotid arteries in adult male rats (CCH group). The identical operations were performed on sham rats without arteries ligation (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In addition, CCH resulting from the permanent BCCAL is linked with the development of neurodegenerative changes, including impaired BBB permeability, synaptic dysfunction, altered brain-carbohydrate metabolism, neuronal loss, and oxidative stress [25][26][27]. Meanwhile, some studies reported the limitation of utilising BCCAL to model for CCH, including the variability of the outcome associated with the duration of cerebral hypoperfusion and the compensatory vascular mechanism that could not prevent neuronal death [28,29]. In support of vascular contributions to delirium, considerable evidence has reported the co-existence of CCH in delirium [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CCH resulting from the permanent BCCAL is linked with the development of neurodegenerative changes, including impaired BBB permeability, synaptic dysfunction, altered brain-carbohydrate metabolism, neuronal loss, and oxidative stress [25][26][27]. Meanwhile, some studies reported the limitation of utilising BCCAL to model for CCH, including the variability of the outcome associated with the duration of cerebral hypoperfusion and the compensatory vascular mechanism that could not prevent neuronal death [28,29]. In support of vascular contributions to delirium, considerable evidence has reported the co-existence of CCH in delirium [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) applying [ 18 F]-2-fluoro-deoxy-D-glucose ([ 18 F]F-FDG) is supposed to be of significant potential to decipher subtle brain metabolic alterations that precede the appearance of morphological cerebral changes. Based on research data [ 18 F]F-FDG brain hypometabolism is a promising biomarker of AD [16]. According to prior studies reporting decreased [ 18 F]F-FDG accumulation of the amygdala, the entorhinal cortex, and the hippocampus, [ 18 F]F-FDG PET appeared to be feasible in the identification of AD-associated brain metabolic patterns in a Wistar male rat model of chronic cerebral hypoperfusion (CCH) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research data [ 18 F]F-FDG brain hypometabolism is a promising biomarker of AD [16]. According to prior studies reporting decreased [ 18 F]F-FDG accumulation of the amygdala, the entorhinal cortex, and the hippocampus, [ 18 F]F-FDG PET appeared to be feasible in the identification of AD-associated brain metabolic patterns in a Wistar male rat model of chronic cerebral hypoperfusion (CCH) [17]. In another study, the development of neurodegeneration was strengthened by-amongst others-the serial registration of [ 18 F]F-FDG hypometabolism of the anterodorsal hippocampus in rats with bilateral common carotid artery ligation-based CCH [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Finally, rodent studies report that chronic cerebral hypoperfusion may trigger Alzheimer pathology, that is, Aβ and, though less consistently, p-tau. 5 However, no study in man so far has addressed the hypothesis that chronic hypoperfusion may cause p-tau accumulation. In the current issue of Stroke , Yamauchi et al 6 report an exploratory cross-sectional positron emission tomography (PET) study that used both a specific fibrillary tau PET radioligand and the standard oxygen-15 PET method to quantitatively map cerebral blood flow, oxygen consumption, and the oxygen extraction fraction (OEF) in 8 patients with symptomatic (transient ischemic attack or minor stroke) chronic unilateral occlusion or severe stenosis of the internal carotid or middle cerebral artery.…”
mentioning
confidence: 99%